Retrospective Analysis of Fondaparinux and Low-Molecular-Weight Heparin in the Treatment of Women With Recurrent Spontaneous Abortion - Zhao, Long; Bi, Shuqin; Fu, Jinhua; Qi, Lijuan; Li, Lin; Fu, Yinghui (Frontiers in Endocrinology, 2021)
Background To compare the clinical efficacy of fondaparinux and LMWH and provide clinical evidence for the effectiveness of fondaparinux in the treatment of recurrent spontaneous abortion caused by PTS. Methods A retrospective analysis was conducted for 120 patients diagnosed with a recurrent spontaneous abortion caused by PTS in Qingdao Jinhua Women’s Hospital from March 2019 to April 2020. The patients were divided into two groups: 68 cases in the control group, treated with LMWH, 52 cases in the observational group, treated with fondaparinux. The pregnancy outcomes and adverse reactions between the two groups of recurrent miscarriage patients were compared. Results No significant difference was detected in the general data between the two groups of patients before treatment (P>0.05). In the observational group, the R value was increased, and the α and MA values were decreased after three months of treatment compared to those before treatment (P<0.05). In the control group, the R value was increased, and the MA value was decreased after three months of treatment compared to those before treatment (P<0.05). After treatment, no significant difference was observed in the pregnancy outcome between the two groups (P>0.05). The total adverse reaction rate of the fondaparinux group was lower than that of the LMWH group (P<0.05). Conclusions In this study, no significant difference was detected in the pregnancy outcome between fondaparinux and LMWH in the treatment of recurrent spontaneous abortion caused by PTS, but fondaparinux had a low occurrence rate of adverse reactions and high safety.